Protective Effect of Ethanol Extract of Kesum Leaves (Polygonum minus) on the Number of Leydig Cells in Mice Exposed to Cadmium Chloride - Paramita, Chici Ayu; Plumeriastuti, Hani; Madyawati, Sri Pantja; Arimbi, Arimbi; Mulyati, Sri; Kurnijasanti, Rochmah (Universitas Airlangga, 2023)
This study aimed to determine the protective effect of ethanol extract of kesum leaves (Polygonum minus) on the number of Leydig cells in mice exposed to cadmium chloride (CdCl2). A total of 20 male mice were divided into five groups, each group consisting of four replications and then given different treatments orally for 21 days. The treatment groups included (K-) 0,5% CMC Na suspension + distilled water, (K+) 0,5% CMC Na suspension + 12 mg/kgBW/day cadmium chloride, (P1, P2, and P3) ethanol extract of kesum leaves, respectively. -respectively 200, 400, and 800 mg/kgBW/day + 12 mg/kgBW/day cadmium chloride. Observations were made by counting the number of Leydig cells. Data were analyzed by ANOVA and Duncan's test. The results showed significant differences (p<0,05) between groups P1, P2, P3 and K+. On the other hand, the P2 group showed similar results to K-. In conclusion, the ethanol extract of kesum leaves can protect and maintain the number of Leydig cells in the testes of mice from exposure to cadmium chloride, and the optimal dose was 400 mg/kgBW/day.